Contribution of Agriculture to the Growth of the Angolan Economy. A look at Bengo province from 2018 to 2021 - Valentim, Ananias (Revista da UI_IPSantarém, 2022)
The present article sought to understand the contribution of agriculture in the economic growth of Angola with a specific look at the province of Bengo, in the period from 2018 to 2021. The relationship between agriculture and economic growth of the regions, the contribution of agriculture in the GDP (Gross Domestic Product) of Angola, the budgetary allocation (in Angola) by sector of activity compared with that of the agriculture sector were analysed. The evolution of agricultural organisations in Bengo, the level of production and employment in this sector were also analysed. The bibliographical and documental method was used with a quantitative approach. The research showed that agriculture has a directly proportional relationship with economic growth, supplies raw material for industry, is a sector that absorbs much labour (even the least qualified). In Angola the agriculture sector, from 2018 to 2021 contributes positively to GDP (its contribution during this period was not above 6%). Agriculture in Bengo has been experiencing some advances, although far from its potential. Bengo has recorded increases in the numbers of agricultural organisations (farms, cooperatives, and associations) from 2019 to 2021. In practical terms, for several reasons such as difficult access to commercial areas, lack of funding, land conflicts led to the non-functioning of many of these created organizations and, others, legally are in illegality. There was an increase in production, except for the year 2021, when there was a sharp drop of 79.84%. By the year 2021 more than 140,000 jobs had been created.